Cestodes of the family Dilepididae (Cestoda:Cyclophyllidea) from fish-eating birds in Mexico: a survey of species - Scholz, Tomás; Kuchta, Roman; Salgado-Madonado, Guillermo (Systematic parasitology, 2002)
A survey of adults of dilepidid tapeworms (Cyclophyllidea) from piscivorous birds from Mexico is presented on the basis of the taxonomic evaluation of freshly collected and voucher specimens. The following species are reported (first records from Mexico marked with an asterisk): Cyclustera capito (Rudolphi, 1819); *C. ibisae (Schmidt & Bush, 1972); *Dendrouterina ardeae Rausch, 1955; *D. herodiae Fuhrmann, 1912; *D. papillifera (Fuhrmann, 1908); Glossocercus auritus (Rudolphi, 1819); *Neogryporhynchus cheilancristrotus (Wedl, 1855); Paradilepis caballeroi Rysavy & Macko, 1973; Paradilepis sp.; Parvitaenia cochlearii Coil, 1955; and Valipora mutabilis Linton, 1927. Dendrouteria herodiae is reported from America for the first time. New definitive hosts are Phalacrocorax olivaceus for C. capito, N. cheilancristrotus and P. caballeroi; Casmerodius albus and Egretta thula for G. auritus; and E. thula for D. herodiae. Data on the morphology of the rostellar hooks of all species, their hosts and distribution in Mexico are provided.
Keywords: Intestines; Female; Animals; Mexiko; ptáci; ženské pohlaví; Birds; zvířata; střeva; Mexico; Cestoda